Duck & Goose, honk! quack! boo! - Hills, Tad (New York Schwartz & Wade Books, 2017)
Duck and Goose, dressed for Halloween as a ghost and a superhero, respectively, go trick-or-treating in the forest, but they are careful to follow Thistle's warning to look out for a scary swamp monster.
Horn Book
Kirkus Reviews
Publishers Weekly
School Library Journal
2.8
P-2
Keywords: Halloween -- Fiction; Costume -- Fiction; Ducks -- Fiction; Geese -- Fiction; Halloween -- Fiction; Costume -- Fiction; Ducks -- Fiction; Geese -- Fiction